RELATIONSHIP BETWEEN STRESS LEVELS AND ONLINE GAME ADDICTION IN ADOLESCENTS - Nur Hidaayah; Esti Yunitasari; Hanik Endang Nihayati; Imamatul Faizah; Hilliyatul Aulia Makhsusoh; Nunik Purwanti (Nurse and Health: Jurnal Keperawatan, 2021)
Background: Factors that trigger stress in adolescents are academic, interpersonal, and family stress. The teenager will feel happy just by playing various game online applications contained in smartphones, but the problems that were previously faced were not resolved. Objectives: This study aimed to determine the relationship between stress levels and online game addiction in adolescents at Hidayatul Ummah High School Surabaya. Methods: This study used an observational approach with a cross-sectional method. The population in this study were all students of classes X, XI, and XII, totaling 80 students. The sample size is 80 students with the Simple Random Sampling method. Data analysis using Spearman Rank test. The variables in this study are stress levels and online game addiction. The instrument used to measure stress level is a Perceived Stress Score (PSS) and Measurement of game addiction using the Indonesian Online Game Addiction Questionnaire. Results: The results of data analysis using the Spearman Rank test with the results = 0.002 which means there is a significant relationship between stress levels and online game addiction in adolescents at Hidayatul Ummah High School Surabaya. The results in this study were the students of grades X, XI, and XII at Hidayatul Ummah High School Surabaya experienced a moderate level of stress with online game addiction in the category of severe addiction. Conclusion: The level of stress with online game addiction carried out at Hidayatul Ummah High School Surabaya mostly experienced moderate stress levels and heavy category addiction to online games.